A97 TACROLIMUS-ASSOCIATED HEMOLYTIC UREMIC SYNDROME IN A PEDIATRIC LIVER TRANSPLANT RECIPIENT. (26th February 2020) - Wong, K W; Gilmour, S
Abstract: Background: Tacrolimus associated hemolytic uremic syndrome (HUS) has been reported in renal and pediatric cardiac transplantation. Furthermore, in adults receiving liver transplant, there are reports of multiorgan failure, death, and end stage renal failure secondary to tacrolimus induced HUS [J NEPHROL 2003; 16: 580–585]. Although tacrolimus is commonly used in pediatric liver transplantation, there are no reports of the same entity. Aims: To describe a case of tacrolimus induced HUS in a pediatric liver transplant patient and subsequent re-initiation of tacrolimus. Methods: The patient was followed during his hospital admission and after discharge. Results: An 8-year-old male with Progressive Familial Intrahepatic Cholestasis (PFIC) Type III, diagnosed at age 2, presents for living unrelated donor liver transplantation. He was previously well compensated but began to deteriorate in the months leading up to transplant with rising liver enzymes, ascites, and mild encephalopathy after presumed viral gastroenteritis. He receives a left lateral segment liver transplantation and is started on tacrolimus immunosuppression post liver transplant as per protocol. On initiation of tacrolimus, the patient's hemoglobin trends downward to a trough of 59 g/L four days post transplantation. Concurrently, his haptoglobin is <0.10g/L, total bilirubin peaks at 708 umol/L, creatinine rises to a peak of 71 umol/L, urea peaks at 23.0 mmol/L. Platelets reach a nadir at 27x10^9/L, seven days post transplantation. Direct antibody test was negative, and blood cultures remained negative. Given the constellation of hemolytic anemia, thrombocytopenia, and acute kidney injury following initiation of tacrolimus, a diagnosis of atypical HUS is made. Tacrolimus is discontinued, intravenous methylprednisolone is started and the patient is switched to cyclosporine immunosuppression. Both the hemolysis and kidney injury resolve gradually. The patient develops side effects from cyclosporine including hypertension and excessive hair growth. One month post discontinuation of tacrolimus, he is started on sirolimus, while weaning steroids and cyclosporine. Seven weeks post discontinuation of tacrolimus, he is restarted on tacrolimus and is currently tolerating dual immunosuppression with no signs of HUS recurrence. Conclusions: Atypical HUS secondary to tacrolimus post liver transplant in children is a rare entity. In the acute period, discontinuation of tacrolimus is essential to preserve renal function given potentially devastating outcomes seen in adults. Cyclosporine is an alternative immunosuppressive agent used in pediatric solid organ transplantation, although it has also been implicated in causing HUS. Funding Agencies: None